التحولات في العلاقات العربية - الإسرائيلية 2002-2021 وانعكاساتها على مستقبل القضية الفلسطينية - الأمين، مصطفى عثمان (مركز دراسات الشرق الاوسط, 2021)
تسارعت التحولات في العلاقات العربية- الإسرائيلية بعد مبادرة السلام العربية عام 2002 وحتى العام 2021 واتسعت لكافة المجالات خاصة في السنوات التي تولى فيها الرئيس دونالد ترامب السلطة في الولايات المتحدة مع استمرار حكومة بنيامين نتنياهو في إسرائيل. وقد شملت التحولات الجوانب الأمنية والاقتصادية والسياسية، ووصلت لدرجة التطبيع الكامل للعلاقات بالتوقيع على معاهدات سلام بين كل من الإمارات والبحرين مع إسرائيل برعاية الرئيس الأمريكي ترامب في واشنطن عام 2020. ويستقصي هذا البحث أهم هذه التحولات التي حدثت في هذه الفترة، والدوافع وراءها، وتحليل البيئة المحلية والإقليمية والدولية المحيطة بها، وتأثيراتها عليها وانعكاساتها على القضية الفلسطينية، إضافة إلى محاولة استشراف مستقبل هذه التحولات. وقد استخدم البحث المنهج الاستقرائي التاريخي والتحليلي والمنهج المقارن، بغرض تحليل ونقد المادة العلمية التي جمعت بعد تصنيفها إلى مجموعات بعناوين فرعية. وقد خلص البحث إلى أن هذه التحولات تمثل خروجا واضحا على الموقف العربي الجماعي وعلى مبادرة السلام العربية، وتحولا استراتيجيا في المبدأ الذي قامت عليه، ولها انعكاسات خطيرة، كما تحمل مخاطر جمة على الأمن القومي العربي وعلى مستقبل القضية الفلسطينية. ومن خلال رصد مستقبل هذه التحولات خلص البحث إلى ثلاثة سيناريوهات: الأول استمرار هذه الاختراقات التطبيعية في ظل استمرار الضعف العربي والتوتر مع إيران، وانحياز الولايات المتحدة لإسرائيل، والانقسام الفلسطيني، والثاني توقفها وتراجعها في ظل إنجازات المقاومة الفلسطينية مؤخرا وتوحد الشعب الفلسطيني في الداخل والخارج مع دعم الشعوب العربية والإسلامية لها، ما قد يحدث تحولا في المواقف العربية والإسلامية والدولية، والثالث استئناف المفاوضات على ضوء قرارات الشرعية الدولية مع ضغط دولي باتجاه تحقيق سلام نهائي يقود لتطبيع كامل بين العرب وإسرائيل، وقد رجح البحث تحقق السيناريو الأول.
The transformations in Arab-Israeli relations accelerated after the Arab Peace Initiative in 2002 until 2021 and expanded in all areas, especially in the recent years in which President Donald Trump took power in the United States and Benjamin Netanyahu in Israel. The transformations included the security, economic and political aspects. They reached the point of full normalization of relations with the signing of the peace treaty between the UAE, Bahrain, and Israel under the auspices of US President Trump in Washington in 2020. These transformations represent a clear departure from the collective Arab position on which the Arab Peace Initiative was founded and bear many risks to Arab national security and the future of the Palestinian cause. This research investigates the most important of these transformations that occurred in this period, the motives behind them, and the analysis of the local and regional environment And the international community, in which these transformations took place, and their effects on them and their repercussions on the Palestinian cause, in addition to anticipating the future for these transformations. After being grouped under subtitles, the study used the historical, analytical, and comparative extrapolation method to analyze and criticize the collected scientific material. The research concluded that these transformations that occurred during this period represent a departure from the Arab Peace Initiative and a strategic shift from the underlying principle and have serious repercussions. By monitoring the future of these transformations, the research concluded three scenarios: First: The continuation of these normalization breakthroughs in light of the continuation of the Palestinian division, Arab fragmentation, tension with Iran, and the bias of the United States towards Israel. Second: Its halt and decline, in light of the strong positions demonstrated by the Palestinian resistance recently in Gaza and the unification of the Palestinian people at home and abroad, which has received strong support from the Arab and Islamic peoples and is expected that there will be a shift in Arab, Islamic and international attitudes. Third: The scenario of resuming negotiations in the light of international legitimacy resolutions, which, if successful, will lead to a final peace that will lead to full normalization between the Arabs and Israel. The study suggested that the first scenario would be achieved.
Keywords: القضية الفلسطينية -- الاحتلال الإسرائيلي -- السياسة الأمريكية -- مبادرة السلام العربية -- التطبيع العربي الإسرائيلي -- العلاقات العربية الإسرائيلية